2012
DOI: 10.3346/jkms.2012.27.12.1569
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sperm Selection Using Hyaluronic Acid Binding in Intracytoplasmic Sperm Injection Cycles: A Sibling Oocyte Study

Abstract: The purpose of this study was to investigate whether sperm selection by hyaluronic acid (HA) binding could improve fertilization rate and embryo quality in intracytoplasmic sperm injection (ICSI) cycles. Two hundred nineteen oocytes obtained from eighteen women were injected with either HA-bound (n = 107) or conventionally selected spermatozoa (n = 112) in a randomized way. All of the participants were infertile couples who had normal sperm parameters but low fertilization rate in previous in vitro fertilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…Our study was undertaken in the hope to identify patient populations where unnecessary PICSI could be avoided. The basic premise of our study was similar to the study carried out by Choe et al [18] who investigated the efficacy of HA sperm selection in a specific patient group with previous poor fertilizations or repeated implantation failures despite having normal semen parameters. The authors reported no benefit in terms of fertilization or embryo quality in such patients.…”
Section: Discussionmentioning
confidence: 80%
“…Our study was undertaken in the hope to identify patient populations where unnecessary PICSI could be avoided. The basic premise of our study was similar to the study carried out by Choe et al [18] who investigated the efficacy of HA sperm selection in a specific patient group with previous poor fertilizations or repeated implantation failures despite having normal semen parameters. The authors reported no benefit in terms of fertilization or embryo quality in such patients.…”
Section: Discussionmentioning
confidence: 80%
“…In two further reports, no association was found between HA binding and FR, fragmentation, and embryo quality though they used washed sperm [Choe et al 2012;Tarozzi et al 2009]. In another report the clinical outcome of sperm functional assays including HBA was studied [Nijs et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these facts, recently, the HABM and ZPP have been bolded as two methods, which are able to potentially recover the spermatozoa with lower DNA damage and higher chromatin condensation (Chan et al, ; Choe et al, ; Hossein Nasr Esfahani et al, ; Parmegiani, Cognigni, Ciampaglia, et al, ; Razavi et al, ). In this line, it is shown that the spermatozoa with a binding ability to HA represent a uniform normal shape (Razavi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the zeta preparation procedure (ZPP) and HA‐binding method (HABM) have considered as more effective methods in assisting technology (Chan, Jacobson, Corselli, & Patton, ; Choe et al, ; Hossein Nasr Esfahani, Deemeh, Tavalaee, Sekhavati, & Gourabi, ; Parmegiani, Cognigni, Ciampaglia, et al, ). Indeed, hyaluronic acid (HA) is a member of the glycosaminoglycan family, which it is highly detectable in the extracellular matrix of the cumulus oophorus.…”
Section: Introductionmentioning
confidence: 99%